2017
DOI: 10.1073/pnas.1701002114
|View full text |Cite
|
Sign up to set email alerts
|

Selective replication of oncolytic virus M1 results in a bystander killing effect that is potentiated by Smac mimetics

Abstract: Oncolytic virotherapy is a treatment modality that uses native or genetically modified viruses that selectively replicate in and kill tumor cells. Viruses represent a type of pathogen-associated molecular pattern and thereby induce the up-regulation of dozens of cytokines via activating the host innate immune system. Second mitochondria-derived activator of caspases (Smac) mimetic compounds (SMCs), which antagonize the function of inhibitor of apoptosis proteins (IAPs) and induce apoptosis, sensitize tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…The efficacy of Smac mimetics relies on sufficient quantities of TNF, which can be augmented by other means, including innate immune stimuli [47][48][49], p38, MK2, or caspase inhibitors [37,50]. Although high levels of TNF can be a concern in regard to safety, these combinations have been proven to be well-tolerated in mice [37,47,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of Smac mimetics relies on sufficient quantities of TNF, which can be augmented by other means, including innate immune stimuli [47][48][49], p38, MK2, or caspase inhibitors [37,50]. Although high levels of TNF can be a concern in regard to safety, these combinations have been proven to be well-tolerated in mice [37,47,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, our team identified M1, a strain of alphavirus isolated from culicine mosquitoes in the Hainan Province of China, as a novel OV capable of inducing endoplasmic reticulum (ER) stress-mediated apoptosis in zinc-finger antiviral protein-deficient cancer cells 25,26 . A series of small-molecule synergists have been found to magnify viral replication-mediated killing in vitro (cell lines), ex vivo (human tumor tissues), and in vivo (T celldeficient nude mice) [27][28][29][30] . Relevant studies have shown that potent T-cell responses are required for the marked efficacy of cancer immunotherapy 9,11 ; hence, T cells, especially cytotoxic CD8 + T cells, are probably critical to the efficacy of M1, although these cells may also mediate rapid viral elimination.…”
Section: Introductionmentioning
confidence: 99%
“…Smac mimetics have been shown to sensitize tumor cells to OVs and other anticancer agents 9, 10, 11. Oncolytic adenoviruses and vaccinia virus armed with Smac also greatly enhanced their antitumor effects 12, 13, 14, 15, 16.…”
Section: Introductionmentioning
confidence: 99%